Acute exacerbations of idiopathic pulmonary fibrosis: tough to define; tougher to manage. Issue 5 (19th May 2017) - Hambly, Nathan; Cox, Gerard; Kolb, Martin
Idiopathic pulmonary fibrosis (IPF) is a chronic, often fatal fibrotic lung disease that typically affects adults over the age of 60 [1]. The disease is characterised by progressive fibrosis of the lung interstitium, which is associated with pronounced architectural distortion, a decline in lung volumes, and impaired gas exchange. The average survival from the time of diagnosis is between 3 and 5 years [2]. There is significant heterogeneity, however, among individual patients as the clinical course is both variable and unpredictable [3]. Some patients have a protracted course with little functional impairment. In others, periods of relative stability can be punctuated by an acute respiratory worsening, labelled as acute exacerbations of IPF that can precipitate dramatic respiratory failure [4]. Rarely, acute exacerbation of IPF is the initial manifestation of IPF leading to death within months. Nintedanib reduces the rate of acute exacerbation in IPF and may improve survival after an acute deterioration http://ow.ly/ezng30b7SGu